The Misrepresentation as a Reason of Rescission of Contract - Popov, Danica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Sometimes a person may enter into a contract as a result of a statement made to him which is false. If the statement is a term of the contract he will have a remedy for breach of contract. If the statement is not a term of the contract it is called a mere misrepresentation, and the consequence is rescission of contract. A misrepresentation is an untrue statement of fact which is one of the causes which induces the contract. A misrepresentation is statement, or conduct, which conveys a false or wrong impression. A contract may be rescined on the ground of misrepresentation even if innocent. An innocent misrepresentation is one made with reasonable ground for beliving it to be true, as where an honest mistake is made. The types of misrepresentation are various. Acording to the Obligation Act it is not any misrepresentation cause the rescind of contract, but only the importance one. The importance misrepresentations are: the error in supstantia and error in personae if the contract is made bearing in mind intuitu personae contract. This paper explanes diferent kinds of misrepresentation giving some proposal for legal interpretation of the provisions of  the Obligation Act. The misrepresentation means an untrue statement of facts, made by one party to the other in the course of negotiating a contract, that induces the other party to enter into the contract. The person making the misrepresentation is called the representor, and the person whom it is made is the representee. A false of fraudulent misrepresentation is one made with knowledge of its falsehood, and intended to deceive. In the case of fraudulent misrepresentation representor did not honestly believe in the truth of his statement, which is not the same as saying that he knew it to be false. A negligent misrepresentation is one made with no reasonable grounds for believing in to be true. An innocent misrepresentation is one made with reasonable grounds for believing in to the true, as where an honest mistake is made. A fraudulent misrepresentation is actionable as a tort. When a person has been induced to enter into a contract by misrepresentation, he may in general either (1) affirm the contract and insist of the misrepresentation being made good, if that is possible, or (2) rescind the contract if it is still executory, and if all parties can be restored to their original positions, or (3) bring an action for damages, or (4) rely upon the misrepresentation as a defence to an action on the contract. A contract may be rescinded of the ground of misrepresentation even if innocent. Specific performance will not be decreed if a definite untrue representation has been relied on. It is clear that the claim for damages for fraudulent misrepresentation  is a claim in tort. So the general governing rule is that the plaintiff should be restored to the position he would have been in if the representation had not been made. In the article is also analyzed comparative law related on misrepresentaton.